The potential role and application of PARP inhibitors in cancer treatment - Chalmers, Anthony J. (British medical bulletin, 2009)
Background Since many anti-cancer agents act by inflicting DNA damage on tumour cells, there is increasing interest in the use of inhibitors of DNA repair to increase the cytotoxicity of these agents. Poly(ADP-ribose) polymerase (PARP) is an abundant nuclear enzyme that binds to sites of DNA damage and promotes repair by modifying a number of key proteins. Potent and specific inhibitors of PARP are available; these have been shown to increase the cytotoxicity of a range of anti-cancer agents including temozolomide, irinotecan and radiation. Sources of data Data from laboratory studies on human tumour cell lines, pre-clinical studies including tumour xenograft models and early phase clinical testing in human subjects are discussed. Areas of agreement Pre-clinical and early clinical testing indicates that PARP inhibitors are extremely well tolerated. As single agents they have activity against BRCA1- and BRCA2-deficient cancers, and in combination they increase the cytotoxic effects of certain chemotherapy agents. Areas of controversy In order for PARP inhibitors to improve outcomes for patients, their sensitizing effects must be tumour specific. Early clinical data indicate that systemic toxicity may be exacerbated, so future trials must address this issue. The mechanism of action of PARP inhibitors in combination with cytotoxic agents is also uncertain. Growing points Among BRCA-deficient cancers, mechanisms of inherent and acquired resistance to PARP inhibitors are under investigation. Combining these agents with radiotherapy appears promising but designing clinical trials to test the efficacy and toxicity of this combination is problematic. Areas timely for developing research A particularly promising role for PARP inhibitors in the treatment of malignant brain tumours is outlined.